P1752THE ROLE OF MTOR INHIBITORS ON CARDIOVASCULAR AGING IN RENAL TRANSPLANT PATIENTS WITH CHRONIC GRAFT DYSFUNCTION. (6th June 2020) - Infante, Barbara; Castellano, Giuseppe; Prisciandaro, Concetta; Dilorenzo, Adelaide; Bellanti, Francesco; Coviello, Nicola; Pontrelli, Paola; Rascio, Federica; FRANZIN, ROSSANA; Gesualdo, Loreto; Serviddio, Gaetano; Grandaliano, Giuseppe; et al.
Abstract: Background and Aims: Chronic Kidney Disease (CKD) is strongly associated with increased circulatory complications that can lead to accelerated cardiovascular aging. During CKD, persistent oxidative stress triggered by mitochondrial dysfunction can affect Klotho protein levels together with circulating FGF23. mTOR pathway is involved in pro-survival mechanism and can be differently modulated by several available therapeutics, therefore exerting central function in senescence, autophagy and cellular regeneration. The aim of this study was to evaluate the beneficial effect of mTOR inhibition on cardiovascular aging in transplanted patient with Chronic Allograft Dysfunction. Method: In this study, 250 transplanted patients with calcineurin inhibitory (CNI) therapy and graft survival higher than 6 months and lower than 60 months were enrolled. The patients were then divided in three groups: (MMF group) patients undergoing CNI therapy with CS (Ciclosporin) and MMF, (mTOR Inhibitors group) patients undergoing CNI, CS and mTOR Inhibitors therapy and (MMF to mTOR Inhibitors group) with patients shifting from MMF to mTOR Inhibitors therapy. Renal function, FGF-23, Klotho, PTH, 1-25OH-Vitamina D, arterial stiffness by Pulse Wave Velocity (PWV), left ventricular hypertrophy expressed by the MSV and endothelial function by Flow Mediated Dilation (FMD) were measured. PBMC were isolated by gradient centrifugation. Results: Between the MMF group and the mTOR Inhibitors groups we did not find significant differences in renal function, PTH, 1-25OH-Vitamina D, PRA, DSA, PWV, FM e DFE. However, FGF23, Klotho, phosphate levels were significantly changed. (FGF-23 pg/ml; p=0, 00001; Klotho p=0, 01; fosfaturia p=0, 03; MMF group vs mTOR Inhibitors group) Interestingly, mTOR Inhibitors group patients showed a higher O2 consumption level associated to increased mitochondrial respiratory function. Pentraxin 3 (PTX-3) and p21 as inflammaging and senescence biomarkers were also detected to be significantly increased in MMF group compared to mTOR Inhibitors group (p=0, 002). Conclusion: In conclusion these data suggest that the use of mTOR Inhibitors in transplanted patients could prevent the occurrence of circulating complication and reduce the cardiovascular aging risk.